IMPLEMENTASI PENEGAKAN DISIPLIN PEGAWAI NEGERI SIPIL BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI TENGAH - Abd Karim, Firdaus MG. (Katalogis, 2015)
The research aimed to describe and analyze the process of policy implementation in the civil service disciplinary Provincial Service Civil Agency of Central Sulawesi Province and supporting factors and obstacles in the process of implementation disciplinary policy of civil servant. The method used qualitative research with descriptive method, five informants and was chosen by purposive sampling. The data collection technique consisted of interviews, observation and documentation. Results of the research explained that the implementation of the Civil servants discipline because four dimensions that were examined, there were four dimensions were not going well, namely: first, especially communication socialization aspect was not optimal, both for human resources sufficient quantity, funding, facilities and infrastructure showed inadequate results. Third, dispositions were attitudes that supported the implementor include honesty, demokratif and commitment have been done by the implementor but has not maximum yet, therefore, its implementation has not became effective yet. Fourth, the bureaucratic structure that the main duties and functions were clear that there was not fragmentation and be flexible.